POTENSI RETRIBUSI PARKIR DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) KABUPATEN GIANYAR - Ni Nyoman Sri Ratnawati (Forum Manajemen, 2012)
The applicability of the law Number 32 of 2004 concerning RegionalGoverment and the law Number 33 of 2004 concerning Financial Equalizationbetwen the Central Goverment and the Regional Goverment, has led to a new eraof how the government is implemented in the regions so that more responsibilitiescan be assumed for attending to decentralized matter. Therefore Gianyar Regencyis always made to make the effort to increase its revenues. Local government localcontains of Original Local Government Income, equilibrium cost and other legallysources. Parking retribution as one of original local government income, remainingthat Gianyar regency, it is needed to give attention optimally for the real parkingretribution potency as a based on taking policy in parking retribution collectionsystem. So the potencial to be developed because it can increase the contribution,growth is also quite effective in increasing the revenue developed area in Gianyarregency.